Peningkatan Value Added dan Product Quality Produk Olahan Lidah Buaya melalui Metode PLA pada UMKM Tirtha Shanum - Kusufa, Roni Alim Ba'diya; Firdaus, Riril Mardiana; Dwanoko, Yoyok Seby; Meviana, Ika; Andiyansya, Moch Farid (STIE Malangkucecwara, 2023)
The UMKM actors will get value added to the results of their business when the management of the output of production is done in a proper and correct way. Good added value can be seen in good production outputs, attractive packaging, healthy, hygienic, safe, and have a lot of flavor variations and are acceptable to the wider market. In addition to value added, product quality also has a very important role for every entrepreneur in running their business. Product quality is among the relatively most influential aspects of product purchase decisions. The objective of this activity is to help solve the problem of UMKM Tirtha Shanum, which is the production of crocodile processing. The approach offered to help partner issues is Participatory Learning and Action (PLA). Participatory Learning and Action (PLA) approaches are characterized by socialization, discussion, and practical training in person. Product processing innovations evolved by creating a variety of processed products based on crocodile tongue. UMKM Tirtha Shanum also processed the crocodile tongue plant into a coconut tongue beverage with bottle and cup siller packaging, candy crocus tongue packaging tubes toples and standing pounc window ziplock sealer, and coconut Tongue powder packaging paper standing Pounc.